Plastidial retrograde modulation of light and hormonal signaling: an odyssey. Issue 3 (4th February 2021) - Jiang, Jishan; Dehesh, Katayoon
Summary: The transition from an engulfed autonomous unicellular photosynthetic bacterium to a semiautonomous endosymbiont plastid was accompanied by the transfer of genetic material from the endosymbiont to the nuclear genome of the host, followed by the establishment of plastid‐to‐nucleus (retrograde) signaling. The retrograde coordinated activities of the two subcellular genomes ensure chloroplast biogenesis and function as the photosynthetic hub and sensing and signaling center that tailors growth‐regulating and adaptive processes. This review specifically focuses on the current knowledge of selected stress‐induced retrograde signals, genomes uncoupled 1 (GUN1), methylerythritol cyclodiphosphate (MEcPP), apocarotenoid and β‐cyclocitral, and 3′‐phosphoadenosine 5′‐phosphate (PAP), which evolved to establish the photoautotrophic lifestyle and are instrumental in the integration of light and hormonal signaling networks to ultimately fashion adaptive responses in an ever‐changing environment.